Reframing a global public relations practice: identifying global capability framework from Asian perspective - Abdullah, Zulhamri; Mohamad, Bahtiar; Raza, Syed Hassan; Mohd Hasan, Nurul Ain (Elsevier BV, 2023)
Reframing public relations for a changing world remains a significant challenge. This study presents a three-year research project intended to propose the Capability Framework for public relations practitioners, employers/consultants, and academic communities in Malaysia. It has validated the three capabilities categories: communication, organisational, and professional, as encapsulated in Anne and Fawkes's Global Capability Framework. The study employed a mixed-method approach with a dominant qualitative component. In the first part, the Delphi method was conducted to understand the fundamental issue of acceptability of the Global Capability Framework. Secondly, the study included an online survey that provided descriptive results about variations in the Global Capability Framework's applicability within the Malaysian context. For the final part, interviews were organised to explore the views of three PR communities on the Global Capability Framework at the individual, organisational, and professional levels in Malaysia. This study is the first attempt to provide a comprehensive Global Capability Framework for the Malaysian context. We found that cultural capability should emerge as a new dimension of this framework in Malaysia's PR context. Hence, this study will benefit all PR communities in standardising and delivering a country-specific capability approach based on the Global Capability Framework to deal with national and global challenges in an increasingly complex world.